Anti-inflammatory spiroditerpenoids from Penicillium bialowiezense - Kwon, Jaeyoung; Kim, Min Jee; Kim, D.-C.; Kwon, H.; Ryu, S.M.; Shim, S.H.; Guo, Y.; Hong, S.-B.; Yim, J.H.; Kim, Y.-C.; Oh, H.; Lee, D. (Academic Press Inc., 2021)
Inflammation is a vital process that maintains tissue homeostasis. However, it is widely known that uncontrolled inflammation can contribute to the development of various diseases. This study aimed to discover anti-inflammatory metabolites from Penicillium bialowiezense. Seven spiroditerpenoids, including two new compounds, breviones P and Q (1 and 2), were isolated and characterized by various spectroscopic and spectrometric methods. All isolated compounds were initially tested for their inhibitory effects against lipopolysaccharide-induced nitric oxide (NO) production in RAW 264.7 macrophages. Of these, brevione A (3) exhibited this activity with a half-maximal inhibitory concentration value of 9.5 μM. Further mechanistic studies demonstrated that 3 could suppress the expression of pro-inflammatory cytokines and mediators, such as NO, prostaglandin E2, interleukin (IL)-1β, tumor necrosis factor-α, IL-6, and IL-12 by inhibiting the activation of nuclear factor-kappa B and c-Jun N-terminal kinase. ？ 2021 Elsevier Inc.